KONSEP DIRI DAN KEMANDIRIAN DENGAN KECEMASAN PADA SISWA KELAS X DAN XI - Nurhidayah, Siti; Pramintari, Ratna Duhita; Verawati, Natalia (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2015)
School is an institution that has an obligation to provide education to develop students'competencies. Lately our society are often exposed to violence, including the violence in schools. As if violence has become part of their culture. This study aimed to determine the relationship of self-concept and self-reliance to anxiety in children victims of bullying .This research was conducted in SMA Yadika 4 Bekasi and data was collected on March (27-28th) 2013. The sampling of this research was 46 students that was selected by total sampling technique. The sample criteria of this research were grade Xand XI students. The Result showed  moderate level of Self-concept in students( 95.7 %) . The prevalence of Self-reliance in students were 100% high . Students at SMA Yadika 4 Bekasi showed moderate level of Anxiety (89.1 %). There is the opposite relationship between self-concept and self-reliance ( r xy = -0.579 ) , meaning that there is the opposite relationship between variabels. if Self-concept level of students were high, so they will have low level of Self-reliance. Vice versa, ifSelf-concept level of students were low, so they will have high level ofSelf-reliance. There is no significant relationship between self-reliance and anxiety ( rxy = 0.297)